In Amateur Death. A Reflection on Snuff Movies (Itinera, 2024)
The study of amateur cinema gives rise to ethical and aesthetic dilemmas that are well- known to anyone who has engaged in such research (see, for example, Caneppele 2022). However, there has been little attention paid to a particular and extreme type of film that, while sharing stylistic features and production methods with amateur cinema, differs significantly in content: snuff movies. The term snuff movie is used to describe films or videos that depict scenes of real violence, including torture, murder, and rape. Although the revulsion provoked by such imagery confines this genre to a limited audience, it is evident that interrogating the manifestations of violence when captured on film (even if done in an amateurish manner) can rekindle dormant discussions on the essence of the medium. Even if unconsciously, Pasolini begins his examination of the sequence plan from a snuff movie, the most famous of which is the Kennedy assassination filmed by Zapruder (Pasolini 1967). Furthermore, ethical concerns pertaining to death and cinema are extensively discussed by Bazin (Bazin 1951). More recently, Nancy has addressed the issue of violence in and of images (Nancy 2002). The three cases presented here illustrate the dilemmas underlying reflections on cinema, which have been accelerated by the exponential expansion of digital amateur cinema. With the spread of smartphones, any murder or suicide has the potential to become a snuff movie, as evidenced by the growth of dedicated telegram channels, which have replaced the older “shock sites” and the circulation of images in the obscure world of the deep web. These images are often leaked from judicial investigations. It is evident that these images are not intended for public viewing. Nevertheless, they exist, they spread, and they intrigue. This contribution is not intended as a definitive theorization of the snuff film, but rather as a starting point, a proposal that – starting from a review of some distinctive formal and productive features common to all the artefacts more or less correctly identified as snuff films – may initiate a reflection that contextualizes these products within the studies of amateur cinema, trying to trace the reasons why these stylistic peculiarities may correspond to a greater degree of realism in the perception of the “spectator”.
Keywords: Snuff Movies, Amateur Films, Death, Web, Pornography, Violence